New frontiers in artificial intelligence : JSAI-isAI 2018 Workshops, JURISIN, AI-Biz, SKL, LENLS, IDAA, Yokohama, Japan, November 12-14, 2018, Revised selected papers /: JSAI-isAI 2018 Workshops, JURISIN, AI-Biz, SKL, LENLS, IDAA, Yokohama, Japan, November 12-14, 2018, Revised selected papers. (2019) - Unknown
No abstract available